The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1242/dev.069575
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocytic Atf4 regulates osteoblast differentiation and function via Ihh

Abstract: SUMMARYAtf4 is a leucine zipper-containing transcription factor that activates osteocalcin (Ocn) in osteoblasts and indian hedgehog (Ihh) ;Col2a1-Atf4, but not Atf4 -/-cartilage, corrects the differentiation defects of Atf4 -/-bone marrow stromal cells and Ihh-blocking antibody eliminates this effect. Together, these data indicate that Atf4 in chondrocytes is required for normal Ihh expression and for its paracrine effect on osteoblast differentiation. Therefore, the cell-autonomous role of Atf4 in chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Unsurprisingly, chondrocyte-selective deletion of collagen type II resulted in smaller mice with shorter bones and thinner trabeculae [25]. Interestingly, a recent paper describes the role of chondrocyte-specific ATF4 (Activating Transcription Factor 4) in bone development and architecture [26]. Akin to our findings, the authors showed that chondrocyte-selective ATF4 deficiency (as opposed to TIMP3 overexpression) also delayed formation of ossification centers, resulted in short bones and also decreased bone mass and osteoblast differentiation; which were all rescued by cartilage-selective ATF4 overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, chondrocyte-selective deletion of collagen type II resulted in smaller mice with shorter bones and thinner trabeculae [25]. Interestingly, a recent paper describes the role of chondrocyte-specific ATF4 (Activating Transcription Factor 4) in bone development and architecture [26]. Akin to our findings, the authors showed that chondrocyte-selective ATF4 deficiency (as opposed to TIMP3 overexpression) also delayed formation of ossification centers, resulted in short bones and also decreased bone mass and osteoblast differentiation; which were all rescued by cartilage-selective ATF4 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that such crosstalk via the transfer of proteins can also occur between articular cartilage and subchondral bone in osteoarthritic joints in vivo [28]. It has also been shown that Ihh and other factors secreted by cartilage can affect osteoblast differentiation and that fibroblast growth factors, BMPs and Wnts might also contribute similarly to this crosstalk [26, 29]. This supports the possibility that TIMP3 expressed by chondrocytes may act on osteoblasts and bone via a paracrine route.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, BMP2 also induced mild ER stress through the PERK/ATF4 pathway in osteogenesis (Saito et al, 2011). Alternatively, ATF4 may modulate osteogenesis through RSK2 (Ribosomal S6 protein kinase 2) (Yang et al, 2004) or regulate growth plate chondrocyte proliferation and differentiation as a transcription factor of Indian hedgehog, a factor required for skeletal development (Wang et al, 2012a). …”
Section: Unfolded Protein Responsementioning
confidence: 99%
“…ATF4 has been shown to play a role in physiological chondrocyte differentiation (Wang et al, 2012a); alteration of that pathway could result in toxicity to chondrocytes. For example, the UPR was induced in zebrafish displaying spinal curvature following treatment with silver nanoparticles (Christen et al, 2013).…”
Section: Unfolded Protein Responsementioning
confidence: 99%
“…Cartilage is not only a precursor of bone but is also an active participant in bone formation, as it secretes local cytokines coupling chondrogenesis and osteogenesis together [3][4][5]. It has been demonstrated that chondrocyte-derived Ihh regulates osteoblast differentiation and function [6,7]. Mice lacking parathyroid hormone (PTH)-related peptide (PTHrP) gene or its receptor, PTH/ PTHrP receptor (PPR), exhibited accelerated hypertrophy of chondrocyte, as well as stimulation of osteoblast differentiation [8,9].…”
Section: Introductionmentioning
confidence: 99%